Review Artikel : Hubungan Umur dengan Demam Tifoid - Diba Masyrofah; Indah Laily Hilmi; Salman Salman (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Typhoid fever is an infectious disease caused by the bacterium Salmonella typhi. This transmission can be through water or food contaminated by the urine and faeces of sufferers containing typhoid germs. This study aimed to determine the number of patients and the causes of typhoid fever as seen from the characteristics of the patients, including the sex and age of the patients (5-11) years and adolescents (12-25) years. Typhoid fever can occur at all ages. Children age 5-11 years old are of school age. This age group often carry out activities outside the home, so they are at risk of being infected with Salmonella typhi, such as snacks at school or outside the home where hygiene is not guaranteed (consuming food and drinks)—contaminated). In compiling this review, the literature study method was used as primary references in the form of national and international journals for the last ten years. Then, in compiling this review using online media, namely Google Scholar. From the results obtained in several journals, Typhoid fever is caused by hygiene and immune factors.